IN-VITRO SCOLICIDAL EFFECTS OF GRAPE AND APPLE VINEGAR ON THE HYDATID CYST PROTSCOLECES - Mokhtaria, Kouidri; Ammar, Selles Sidi Mohammed (Buletin Veteriner Udayana, 2020)
At present, surgery remains the preferred treatment for hydatid cyst. Various chemical scolicidal agents have been used for inactivation of protoscoleces during surgery, but most of them are associated with adverse side effects. In this study we investigated the effect of two commercial grape and apple vinegar on the viability of hydatid cyst protoscoleces. The protoscoleces of E. granulosus were aspirated from the infected livers and lungs of sheep slaughtered at Tiaret abattoir. 0.5 mL of two commercial grape and apple vinegar was used for 5, 10, and 15 min in the experiments. 0.1% eosin staining assessed viability of protoscoleces. All tests were carried in triplicate. The mortality rates of protoscoleces were 100% after 5min, 10 min and 15 min of incubation with grape vinegar and apple vinegar. To conclude, the results of the present survey indicated high scolicidal activity of apple vinegar and grape vinegar against protoscoleces of hydatid cyst and can be used in hydatid cyst surgery. However, further studies will be needed to confirm these results by checking this scolicidal activity in an in-vivo model.